IMPLEMENTATION OF THEMATIC LEARNING IN THE SD N 6 PANJER KEBUMEN - Purwanti, Septy Dewi; Septiningrum, Eka Setya; Hidayat, Akbar Maulana; Hidayah, Ratna (Universitas Sebelas Maret, 2018)
Thematic learning integrates competencies from subjects into themes, which are related to the experience and environment of students.The government requires the transfer of curriculum from KTSP to the 2013 curriculum in the hope of perfecting and overcoming weaknesses in the learning patterns in the previous curriculum. Thematic learning has been implemented in the Kebumen area, one of which is SD N 6 Panjer which has implemented thematic learning in grade I, II, IV, and V. This research want to describe the implementation of thematic learning in SD Negeri 6 Panjer. This research includes qualitative research. Data collection techniques using observation at SD N 6 Panjer. The results showed that the implementation of thematic learning in SD N 6 Panjer in grades I, II, IV, and V was not fully in accordance with the six thematic learning characteristics: 1) student-centered, 2) direct experinces, 3) the separation of subjects was not so clearly, 4) presents the concept of various contents, 5) is flexible, 6) uses the principle of learning while playing.